Two-dimensional speckle tracking echocardiography is useful in early detection of left ventricular impairment in patients with Crohn's disease - (:unkn) unknown (VERDUCI PUBLISHER, 2016)
OBJECTIVE: Crohn's disease (CD) is a chronic inflammatory bowel disease that can affect the entire gastrointestinal tract. Cardiac involvement is considered very rare. Pericarditis, myocarditis, endocarditis, cardiomyopathy and complete heart block are some of the cardiac extraintestinal manifestations of CD. The aim of this study was to explore the left ventricular (LV) functions with two-dimensional (2D) speckle tracking echocardiography (STE) in patients with CD with normal cardiac functions. PATIENTS AND METHODS: We enrolled 50 consecutive patients with CD and 50 age and sex matched healthy controls. All patients underwent a transthoracic echocardiogram with evaluation of LV functions with 2D STE. RESULTS: Baseline characteristics were similar between patients with CD (24 male, mean age: 41.0 +/- 13.9 years) and controls (24 male, mean age: 40.1 +/- 7.3 years). Although conventional echocardiographic parameters were similar between two groups, global longitudinal strain was significantly lower in patients with CD compared to controls (19.6 +/- 3.3 versus 21.2 +/- 2.9, p = 0.014). Correlation analysis revealed that Crohn's Disease Activity Index is inversely correlated with LV global longitudinal strain (r = 0.703, p < 0.001) in patients with CD. We also evaluated inflammatory parameters such as CRP, erythrocyte sedimentation rate, and complete blood counts in patients with CD. Correlation analysis revealed that only platelet value is weakly correlated with Crohn's Disease Activity Index (r = 0.311, p = 0.083). CONCLUSIONS: Crohn's disease is associated with impairment in LV global longitudinal myocardial function. Crohn's Disease Activity Index is also strongly correlated with LV global longitudinal strain. 2D-STE may be an useful method for early detection of LV impairment in patients with CD.
Keywords: Crohn's disease; Left ventricular function; Speckle tracking echocardiography; INFLAMMATORY-BOWEL-DISEASE; STRAIN-RATE; EXTRAINTESTINAL MANIFESTATIONS; CARDIOVASCULAR-DISEASE; MYOCARDIAL-INFARCTION; PERICARDITIS; COMPLICATION; THROMBOSIS; MORTALITY